Scheduling and routing methods for cognitive radio sensor networks in regular topology. Issue 1 (24th June 2014) - Li, Wenxiang; Leung, Victor C.M.; Zhu, Chunsheng; Ma, Yajie
Abstract: Wireless sensor network of regular topology is efficient in area covering and targets locating. However, communications with fixed channels lead to low spectrum efficiency and high probability of conflicts. This paper proposes economical timeslots‐and‐channels allocation methods for scheduling links in square, triangle, and hexagon lattice topologies. Based on these scheduling methods in square lattice, the authors explore routing methods for load balance and delay minimization, respectively, and compare their effects on transmission delay and energy consumption. The OMNet++‐based simulation for square lattice verified the effectiveness of scheduling methods for improving network throughput and made performance comparison among different scheduling methods. It also proved that delay minimization‐oriented routing helps to reduce the energy consumption for node standing by and load balance‐oriented routing helps to reduce the energy consumption for packets transmission. However, there is trade‐off between the reductions of the two types of energy consumptions. The authors further propose the idea of hybrid routing with the two aforementioned routing methods for reducing overall energy consumption and explore the challenges and countermeasures for hybrid routing optimization. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : Propose economical timeslots‐and‐channels allocation and scheduling methods for Square, Triangle, and Hexagon lattice topologies. Explore relevant routing methods for load balance and delay minimization and compare their effects on transmission delay and energy consumption. Analyses show that Square provides greater throughput than Triangle and Hexagon with the scheduling methods. Delay minimization‐oriented routing and load balance‐oriented routing help to reduce the energy consumption for standing by and transmission, respectively. And there is trade‐off between the two types of energy consumptions.